PENGARUH KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN KONVEKSI PT. RIA PANAS SIPOHOLON RPS SERVICE - Lestari, Sri; Rika, Rhofana Rizky (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2022)
The purpose of this study was to determine how much influence Communication and Work Environment on Employee Performance PT. Ria Panas Sipoholon with 48 permanent employees as respondents. The methods used are classical assumption analysis, simple and multiple regression analysis, simple and multiple correlation analysis, coefficient of determination, t test and f test. The results of the multiple correlation analysis that the relationship between communication and work environment with a value of 0.770 or 77.0%, which means it has a strong and positive correlation relationship to employee performance. The result of the coefficient of determination is 0.593, which means that communication and work environment have an effect of 59.3% on employee performance, while the remaining 40.7% is influenced by other factors. The results of the research using the t hypothesis test indicate that communication (X1) has a tcount value of 7.555 with a significant level of 0.000 which means that it partially has a positive and significant effect on employee performance. And the work environment (X2) has a tcount of 5.810 with a significant level of 0.000 which means that it partially has a positive and significant effect on employee performance